PENINGKATAN KETERAMPILAN BERPIKIR KRITIS MELALUI MODEL PEMBELAJARAN DISCOVERY LEARNING - Devi Qurniati; Yayuk Andayani; Muntari - (Postgraduate, University of Mataram, 2015)
The importance of critical thinking skills for students in the study of chemistry, it is necessary to appropriate learning models that can involve students directly in making students active learning and improve students' critical thinking skills. One model that can be applied is discovery learning model learning. The purpose of this study was to determine the increase in critical thinking skills of students learning through discovery learning. This study was an experimental study design with nonequivalent pretest-Posttes Control Group Design. The subjects of the study involves two classes of experimental class and control class. Data collection instruments in the form of test critical thinking skills in the form of matter description. Statistical testing using independent sample t-test were previously tested for normality, homogeneity test at the 0.05 significance level. The results showed no difference in the increase in critical thinking skills in each of the indicators of critical thinking skills.Keywords: Discovery learning, critical thinking skills